2021
DOI: 10.1159/000515459
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Quality of Life after Pancreatic Surgery for Intraductal Papillary Mucinous Neoplasm

Abstract: <b><i>Introduction:</i></b> Intraductal papillary mucinous neoplasms (IPMNs) represent the most common precancerous cystic lesions of the pancreas. The aim of our study was to investigate if resection for non-invasive IPMNs alters quality of life (QoL) in a long-term follow-up. <b><i>Methods:</i></b> Patients (<i>n</i> = 50) included in the analysis were diagnosed and resected from 2010 to 2016. QoL was assessed at a median of 5.5 years after resectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…[17][18][19] Moreover, in the current study, 45% of operated individuals underwent surgery for benign disease, while we know that pancreatic surgery is associated with substantial grade III-IV (Clavien-Dindo) morbidity (4%-31%) and mortality (2%-6%). [20][21][22][23][24] We found CA19.9 levels >37 kU/L not to be associated with the (2020) 10 and others. Ciprani et al 10 proposed 100 kU/L as a new cutoff, which would alter the sensitivity and specificity for PC detection from 41% to 85% (cutoff 37 kU/L), to 23% and 97%.…”
contrasting
confidence: 46%
See 1 more Smart Citation
“…[17][18][19] Moreover, in the current study, 45% of operated individuals underwent surgery for benign disease, while we know that pancreatic surgery is associated with substantial grade III-IV (Clavien-Dindo) morbidity (4%-31%) and mortality (2%-6%). [20][21][22][23][24] We found CA19.9 levels >37 kU/L not to be associated with the (2020) 10 and others. Ciprani et al 10 proposed 100 kU/L as a new cutoff, which would alter the sensitivity and specificity for PC detection from 41% to 85% (cutoff 37 kU/L), to 23% and 97%.…”
contrasting
confidence: 46%
“…Also, we established that this often leads to an intensified follow‐up regimen, which could cause harm due to unnecessary diagnostic procedures (such as EUS/FNA) and psychological distress 17–19 . Moreover, in the current study, 45% of operated individuals underwent surgery for benign disease, while we know that pancreatic surgery is associated with substantial grade III‐IV (Clavien‐Dindo) morbidity (4%–31%) and mortality (2%–6%) 20–24 …”
Section: Discussionmentioning
confidence: 66%
“…5,6 Prior analyses have primarily focused on pancreatic resections for benign pathologies and have shown that QOL worsens in the acute postoperative period. 7,8 However, there is a paucity of long-term QOL data, especially for patients undergoing surgery for pancreas cancer. [7][8][9] As surgery is currently the only known treatment that offers long-term survival for pancreatic cancer, a thorough understanding of posttreatment QOL and any potential longterm GI symptoms may guide patient-centered care discussions.…”
mentioning
confidence: 99%
“…The diagnosis and treatment of pancreatic cancer carry significant emotional, physical, and social costs 5,6 . Prior analyses have primarily focused on pancreatic resections for benign pathologies and have shown that QOL worsens in the acute postoperative period 7,8 . However, there is a paucity of long-term QOL data, especially for patients undergoing surgery for pancreas cancer 7–9 .…”
mentioning
confidence: 99%
“…In addition, consideration of recurrence and long-term survival after surgery for IPMN, TP, and PD might have different operation indications. 2 , 3 Therefore, we think the authors should respectively provide predictors of severe surgical complications and a classification tree for PD and TP.…”
mentioning
confidence: 99%